The Seroprevalence of Toxoplasma gondii in Cats at the House of Maternal Women with Toxoplasmosis in Badung, Indonesia - Subrata, Made; Astawa, Nyoman Mantik; Suryadi, Nyoman Tigeh; Purnama, Sang Gede; Agustina, Kadek Karang; Harjana, Ngakan Putu Anom; Damriyasa, Made (Kesmas, 2021)
Toxoplasmosis is a zoonotic disease caused by infection with the parasite called Toxoplasma gondii (T. gondii). The health and social impacts of the infectionare enormous, including miscarriage, hydrocephalus, blindness, and mental retardation. The occurrence of toxoplasmosis in maternal women cannot be se parated from cats around their houses. This study aimed to determine the seroprevalence of the parasite in cats found in the human carriers residences and identify the risk factors of toxoplasmosis in maternal women in Badung District, Bali Province, Indonesia. A total of 80 cat serum samples were obtained from two residential groups, 40 from the housing where the maternal women were infected and another 40 from where there were no identified sufferers of the disease. All the samples were examined using the enzyme-linked immunosorbent assay (ELISA) method to detect the presence of antibodies T. gondiiin feralcat serum. The results showed that 47.5% of the examined subjects had the said antibodies. As much as 65% came from housing with cases of toxoplasmosisin maternal mothers, and 30% came from residences with none. The presence of feral cats is a major risk factor for the transmission of T. gondiito humans.